Otolaryngology Manifestations of Primary Ciliary Dyskinesia: A Multicenter Study. (March 2022) - Zawawi, Faisal; Shapiro, Adam J.; Dell, Sharon; Wolter, Nikolaus E.; Marchica, Cinzia L.; Knowles, Michael R.; Zariwala, Maimoona A.; Leigh, Margaret W.; Smith, Mariana; Gajardo, Pilar; Daniel, Sam J.
Objective: This project aims to prospectively and objectively assess otolaryngological manifestations and quality of life of children with primary ciliary dyskinesia (PCD) and compare these findings with healthy pediatric controls. Study Design: Cross-sectional. Setting: Two high-volume pediatric PCD specialty centers. Methods: Standardized clinical assessment; Sino-Nasal Outcome Test 22 (SNOT-22); Hearing Environment and Reflection Quality of Life (HEAR-QL); Reflux Symptom Index (RSI); standardized physical examination of the sinonasal, laryngeal, and otological systems; and investigations including pure-tone audiograms (PTAs) and sinonasal cultures were collected. Results: Forty-seven children with PCD and 25 control participants were recruited. Children with PCD had more upper airway symptoms than healthy children. They had significantly higher scores in both SNOT-22 and RSI, indicating worse sinonasal and reflux symptoms, with worse quality of life on the HEAR-QL index compared to healthy children ( P < .05). Fifty-two percent of children with PCD-related hearing loss were not aware of their hearing deficit that was present on audiological assessment, and only 23% of children who had ventilation tubes had chronic otorrhea, most of which was easily controlled with ototopic drops. Furthermore, although all children with PCD had chronic rhinosinusitis, only 36% of them were using topical nasal treatment. The most common bacteria cultured from the middle meatus were Staphylococcus aureus in 11 of 47 (23%), followed by Streptococcus pneumoniae in 10 of 47 (21%). Conclusion: This multisite cohort highlights the importance of otolaryngology involvement in the management of children with PCD. More rigorous otolaryngological management may lead to reductions in overall morbidity and improve quality of life for children with PCD.